PEMETAAN KAWASAN RAWAN BANJIR KABUPATEN LANDAK - Fikriansyah, Irfan; Barlian Soeryamassoeka, Stefanus; Nirmala, Azwa (Jurnal Rekayasa Teknik Sipil dan Lingkungan - CENTECH, 2024)
Flooding is a global natural disaster that occurs frequently, including in the Landak Regency. From several studies that have been conducted in the Landak Regency area, it is known that there has been an increase in the frequency of flooding in the period 1998-2021, and flooding that occurs not only in urban areas but also in rural areas which are upstream of the Landak Sub-watershed. For this reason, information on flood-prone areas in Landak Regency is needed through geospatial maps to minimize flooding in the area. This research aims to map flood-prone areas and determine the classification of flood-prone levels in the Landak Regency. In this research, the data used are (a) data from observation and documentation in the field during floods, (b) data from Focus Group Discussion (FGD) conducted at the hall of the Landak Regency Public Works Office, which discussed flood control strategies in the Landak Subwatershed, (c) data on land slope, land elevation, soil type, land cover, rainfall, river buffer, inundation duration, and inundation height. Then, an overlay of the eight parameters was done, a zoning map of flood-prone areas was made, and the level of the flood-prone regions in Landak Regency was determined. Based on the analysis, the Landak Regency's areas of shallow, low, and moderate vulnerability to flooding are, respectively, 62,819.28 ha (7.58%), 184,504.24 ha (22.28%), 187,524.53 ha (22.64%), high, and very high (19.98%) levels of vulnerability to flooding. Landak Regency's Ngabang Sub-district (53,787.37 ha), Sebangki Sub-district (50,405.59 ha), and Mandor Sub-district (33,800.63 ha), which comprise Sebangki Village, Sungai Segah, Rantau Panjang, Kumpang Tengah, Sumsum, Sekilap, Keramas, Manggang, Amboyo Selatan, and Temiang Sawi, are among the areas with extremely high flood vulnerability.